2012
DOI: 10.2478/v10247-012-0010-1
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial activity as influenced by compaction and straw mulching

Abstract: Soil microbial activity as influenced by compaction and straw mulchingField study was performed on Haplic Luvisol soil to determine the effects of soil compaction and straw mulching on microbial parameters of soil under soybean. Treatments with different compaction were established on unmulched and mulched with straw soil. The effect of soil compaction and straw mulching on the total bacteria number and activities of dehydrogenases, protease, alkaline and acid phosphatases was studied. The results of study ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…These results support previous research into this area on beneficial effects of mulch on soil activity (Tu et al 2006;García-Orenes et al 2010). Under field conditions, mulched soybean showed greater values of dehydrogenases, protease, and acid and alkaline phosphatases than unmulched soil (Siczek and Frąc 2012).…”
Section: Soil Enzymatic Activitysupporting
confidence: 90%
See 1 more Smart Citation
“…These results support previous research into this area on beneficial effects of mulch on soil activity (Tu et al 2006;García-Orenes et al 2010). Under field conditions, mulched soybean showed greater values of dehydrogenases, protease, and acid and alkaline phosphatases than unmulched soil (Siczek and Frąc 2012).…”
Section: Soil Enzymatic Activitysupporting
confidence: 90%
“…However, straw mulch effect on enzymes activities was strongly dependent on mulching levels and some adverse effects at straw mulching higher than 15,000 kg ha -1 were observed (Zhang et al 2015). Straw mulch effect on soil enzymatic activity was also dependent on soil compaction level (Siczek and Frąc 2012). The study of Govaerts et al (2007) indicated that soil microbial biomass C and N was significantly higher for residue retention compared to residue removal in a long-term field experiment.…”
Section: Introductionmentioning
confidence: 94%
“…Terms & Conditions of access and use can be found at http:// www.tandfonline.com/page/terms-and-conditions Introduction Soil is a complex and dynamic biological system, where microorganisms play an important role in transformation of soil organic matter and therefore can affect plants growth. Microorganisms take part in carbon, nitrogen, phosphorus and other macroelements cycles in soil environment and can transform their unavailable form into components available for plants (Magdoff & van Es 2000;Siczek & Frąc 2012). On the other hand, plants can influence microbial community by controlling the quality and quantity of organic substrates that bulk soil contains (Viketoft et al 2005).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…(Nannipieri et al, 2012). Several studies have focused specifically on compost and crop residues, such as straw, used as mulch or soil amendment (Siczek and Frac, 2012;TerAvest et al, 2011). In spite of this and with the exception of plant litter in natural forests and wood chips, very few of these studies address lignocellulosic residues such as those present in almond shells.…”
Section: Introductionmentioning
confidence: 99%